Nematic liquid crystal mixtures for 3D active glasses application. Issue 2 (26th January 2017) - Mazur, R.; Piecek, W.; Raszewski, Z.; Morawiak, P.; Garbat, K.; Chojnowska, O.; Mrukiewicz, M.; Olifierczuk, M.; Kedzierski, J.; Dabrowski, R.; Weglowska, D.
ABSTRACT: Methods of 3D imaging present on the market can be divided into two basic groups: autostereoscopic and stereoscopic. At the stereoscopic methods of 3D imaging it is necessary to use special glasses for separation of images constituting stereo-pair. The most commonly used active glasses consist of two electro-optical transducers based on twisted nematic or other electro-optical effects. Here the evaluation of liquid crystal mixtures is designed intentionally for 3D active glasses in order to eliminate drawbacks of active glasses available on the contemporary market. Material parameters of new designed liquid crystal mixtures such as: elastic constants, viscosity, refractive indices, dielectric and spectral properties as well as response times have been determined. In addition to the symmetrisation of the switching times of 3D active glasses, a dual frequency nematic liquid crystal has been proposed. GRAPHICAL ABSTRACT: